A Note on Bias of Closed-Form Estimators for the Gamma Distribution Derived From Likelihood Equations - Louzada, Francisco; Ramos, Pedro L.; Ramos, Eduardo [UNESP] (Amer Statistical Assoc, 2019)
We discuss here an alternative approach for decreasing the bias of the closed-form estimators for the gamma distribution recently proposed by Ye and Chen in 2017. We show that, the new estimator has also closed-form expression, is positive, and can be computed for n > 2. Moreover, the corrective approach returns better estimates when compared with the former ones.
Keywords: Bias correction; Improve estimators; Two-parameter gamma distribution